TANTANGAN PROFESI SEKRETARIS DI ERA DIGITAL - Risnawati, V. Naniek; Lipursari, A. (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
In today's digital era, the world is experiencing changes and adaptations in facing the challenges and opportunities offered by information and communication technology. The development of technology, especially in the digital era, has become the main driving force in changing all aspects of society, including the secretary profession. This rapid technological progress is a challenge as well as an opportunity for company development. Every individual is required to be able to follow the developments of this increasingly sophisticated era. Likewise with secretaries, they must also blend in and adapt to the developments of the existing digital era. However, there are several challenges that need to be overcome in adapting to the digital world. This article analyzes the influence of the digital era on the transformation of secretarial work, with a focus on the challenges that arise in the digital era.